2016
DOI: 10.1155/2016/4868536
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Mechanisms of Pulmonary Inflammation and Oxidative Imbalance Induced by Exercise

Abstract: The mechanisms involved in the generation of oxidative damage and lung inflammation induced by physical exercise are described. Changes in lung function induced by exercise involve cooling of the airways, fluid evaporation of the epithelial surface, increased contact with polluting substances, and activation of the local and systemic inflammatory response. The present work includes evidence obtained from the different types of exercise in terms of duration and intensity, the effect of both acute performance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 140 publications
0
12
0
1
Order By: Relevance
“…Despite this apparent respiratory reserve, there are several mechanisms by which long-distance running might compromise pulmonary and/or respiratory-muscle function in healthy subjects. First, exercise is associated with airway cooling and/or dehydration and increased contact of the airway with polluting substances; consequently, potential activation of local and systemic inflammatory responses may result in airway obstruction, and negatively influence lung function (for review, see [ 9 ]). Second, marathon running has been associated with a mild, transient, post-race pulmonary oedema [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this apparent respiratory reserve, there are several mechanisms by which long-distance running might compromise pulmonary and/or respiratory-muscle function in healthy subjects. First, exercise is associated with airway cooling and/or dehydration and increased contact of the airway with polluting substances; consequently, potential activation of local and systemic inflammatory responses may result in airway obstruction, and negatively influence lung function (for review, see [ 9 ]). Second, marathon running has been associated with a mild, transient, post-race pulmonary oedema [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…En el ejercicio, los protocolos de corta duración no han reportado cambios en la H2O2CAE (Nowak et al, 2001, Marek et al, 2008. Cuando el ejercicio se realiza por un tiempo superior a dos horas en carreras pedestres al aire libre (Araneda et al, 2012) o sobre noventa minutos en cicloergómetro en condiciones de laboratorio (Araneda et al, 2016) hemos encontrado habitualmente incrementos tanto de la H2O2CAE como de la NO2 -CAE a los 20 y 80 minutos posteriores al cese del ejercicio. Como ya fue mencionado, estos hallazgos son contrarios a los presentados en este trabajo, donde el modelo obtenido evidenció una baja de la NO2 -CAE durante las ocho horas posteriores al ejercicio.…”
Section: Discussionunclassified
“…Airway inflammation in athletes has been poorly described and with controversial results in studies focusing this subject [18, 19]. Bonsignore et al found increases in lymphocytes and eosinophils and a decrease in macrophages in induced sputum after a 5 km race at the beach [20].…”
Section: Discussionmentioning
confidence: 99%
“…The lungs have crucial role in gas exchange, experiencing great modifications of their activity during exercise, in addition to their important role in cardiopulmonary function [19]. Miles et al [29] have reported a reduction in pulmonary diffusing capacity after prolonged exercise, which persisted for a certain period of time.…”
Section: Discussionmentioning
confidence: 99%